2013
DOI: 10.1021/ja407070y
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Directed Functionalization of the Redox-Active Bis(imino)acenaphthene Ligand Class: An Experimental and Theoretical Investigation

Abstract: The synthesis, characterization, and theoretical study of the sterically directed functionalization of the redox-active bis(imino)acenaphthene (BIAN) ligand class has been explored. With dependence on the steric congestion encompassing the N-C-C-N fragment of the Ar-BIAN ligand, functionalization can be directed to proceed either via a radical backbone dearomatization or a nucleophilic imine C-alkylation pathway. The structures of the Ar-BIAN derivatives 14-19 were determined by means of single-crystal X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…A similar alkyl transfer has also been observed in the reaction between n BuLi or MR 3 (M = group 13 metal, R = alkyl substituent) and I in noncoordinating solvents, leading to the formation of a imine-amido complex bearing an alkyl substituent on the carbon adjacent to the amide functionality . More recently Cowley and co-workers also reported the double alkylation of the acenaphthene backbone of I in the C 4 and C 5 positions by tert -butyllithium, via a radical dearomatization, two-electron reduction pathway, leading to the formation of complex V …”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…A similar alkyl transfer has also been observed in the reaction between n BuLi or MR 3 (M = group 13 metal, R = alkyl substituent) and I in noncoordinating solvents, leading to the formation of a imine-amido complex bearing an alkyl substituent on the carbon adjacent to the amide functionality . More recently Cowley and co-workers also reported the double alkylation of the acenaphthene backbone of I in the C 4 and C 5 positions by tert -butyllithium, via a radical dearomatization, two-electron reduction pathway, leading to the formation of complex V …”
Section: Introductionsupporting
confidence: 58%
“…While we have not fully rationalized the synthesis of this chiral, dimerized tetraimine product, we suggest its formation is possibly the result of a sterically induced radical coupling reminiscent of well-precedented reactivity observed for similarly redox inactive 4f-element complexes . In support of this hypothesis, Evans and Cowley have observed a radical anion C 5 -alkylated free radical as an intermediate in the formation of the dialkylated dearomatized lithium complex V …”
Section: Resultsmentioning
confidence: 68%
“…A different type of addition to dpp‐bian was reported by Hill and co‐workers in 2011: the reactions of bulky organometallics, for example, K[CH(SiMe 3 ) 2 ] and M[CH(SiMe 3 ) 2 ] 2 (M=Mg, Ca, Sr), with dpp‐bian led to dearomatization of one of the six‐membered rings by addition of the nucleophile to the naphthalene ring . These processes were studied in detail by Cowley and co‐workers in 2013; they concluded that the functionalization of bians by organometallic species was sterically directed. Apparently, the formation of the complexes 7 and 19 are also sterically controlled processes.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial attempt to decipher the mechanism using electron paramagnetic resonance (EPR) revealed that rather than a 3-electron reduction to generate an anionic Fe species, the formation of a radical anion of the ligand might be taking place. Radical dearomatization of dpp BIAN ligands in the presence of t -BuLi [148,149] and alkylation of dpp BIAN with n -BuLi due to the formation of organic radicals have been reported in the literature [150,151]. Titration of n -BuLi to a solution of dpp BIAN and dpp BIANFeCl 2 in toluene independently indicated a competition between ligand metathesis and complex reduction at each addition of n -BuLi (Scheme 9).…”
Section: Iron-catalyzed Hydrosilylationmentioning
confidence: 91%